1974
DOI: 10.1172/jci107805
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin Diabetes CORRELATION WITH EXTENT OF DEPRESSION OF PANCREATIC ISLET NICOTINAMIDE ADENINE DINUCLEOTIDE

Abstract: A B S T R A C T The diabetogenic activity of streptozotocin has been correlated with a reduction in pyridine nucleotide synthesis in the mouse pancreatic islet. To determine the specificity of this reduction for diabetogenicity, a comparative study of streptozotocin, its cytotoxic moiety, 1-methyl-1-nitrosourea, and alloxan was performed. Streptozotocin administered intraperitoneally (i.p.) producd a dose-related reduction in islet NAD which was proportional to the degree of diabetogenicity. A diabetogenic dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 18 publications
(23 reference statements)
0
38
0
Order By: Relevance
“…The action of STZ on mitochondria generates SOD anions, which leads to diabetic mellitus complications. [19][20][21] Glibenclamide, being as an Sulfonylurea derivative is often used as a standard antidiabetic drug in STZ-induced diabetes to compare the efficacy of a variety of antihyperglycemic drug compounds. Glibenclamide has been involved in stimulating insulin secretion from pancreatic β-cells principally by inhibiting ATP sensitive K + ATP channels in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The action of STZ on mitochondria generates SOD anions, which leads to diabetic mellitus complications. [19][20][21] Glibenclamide, being as an Sulfonylurea derivative is often used as a standard antidiabetic drug in STZ-induced diabetes to compare the efficacy of a variety of antihyperglycemic drug compounds. Glibenclamide has been involved in stimulating insulin secretion from pancreatic β-cells principally by inhibiting ATP sensitive K + ATP channels in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this observation is the report by Dulin et al [19] who showed that in vivo 2-deoxyglucose, but not glucose, glucosamine or mannoheptulose protected against the diabetogenic action of streptozotocin. Yet Anderson et al [25] have demonstrated that the glucose carrier of methyl-14C-streptozotocin facilitates the uptake of its cytotoxic group, 1-methyl-l-nitrosourea, into islets. These authors have also shown that a dose of streptozotocin, which was diabetogenic when administered intra-peritoneally, attained a peak plasma N-nitroso intact streptozotocin concentration of 0.22 mM and thus a concentration in the range of those used in vitro in the present studies.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the administration of nicotinamide, a precursor of NAD in many tissues, protects against the diabetogenic effects of subsequently administered streptozotocin [17][18][19][20][21][22][23][24][25]. This protection may, however, unmask a long term oncogenic effect of the drug [26,27].Studies of the effects of streptozotocin on islets of Langerhans have shown a correlation between the extent of B-cell destruction and the decrease in islet NAD [25]; decreased oxidation of glucose by islets isolated after in vivo administration of a diabetogenic dose of streptozotocin [28]; and a dose-related inhibition of glucose-induced insulin secretion during two hours of incubation, when the drug was added in vitro to isolated islets [29]. The purpose of the present study was that of investigating the effects of streptozotocin on proinsulin synthesis, while simultaneously measuring its effects upon insulin release.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non insulin dependent diabetes mellitus, type 2 (NIDDM) can be manifested by chronic hyperglycemia due to defects in insulin secretion, insulin action and or both [16] . It is common disorder among the Indian population.…”
Section: Introductionmentioning
confidence: 99%